Dual language programs: Questions of access in the state of Arizona - Gomez, Laura M.; Cisneros, Jesus (Education Policy Analysis Archives, 2020)
Public schools across the country are increasingly working with children who enter schools speaking a language other than English. Using a case study methodology, the authors examined Dual Language Program (DLP) implementation in Arizona, which by law supports English-only education. Several benefits (bilingualism, bi-literacy, biculturalism, globalization) and challenges (curriculum, teachers, state policy, funding, and lack of access to DLPs for minority language students) are highlighted from stakeholder perspectives. Participants in this study described the paradox of excluding ELLs from dual language programs as inefficient, unnecessary, and wrong. Taking Interest Convergence as a theoretical framework to understand the Arizona context regarding English-only education, this study raises implications for research and practice.